2015
DOI: 10.1074/jbc.m114.593673
|View full text |Cite
|
Sign up to set email alerts
|

Lignin-rich Enzyme Lignin (LREL), a Cellulase-treated Lignin-Carbohydrate Derived from Plants, Activates Myeloid Dendritic Cells via Toll-like Receptor 4 (TLR4)

Abstract: Background: Although lignins are the second major biomass, their biological activities are little known. Results: Certain barley husk-derived lignin-carbohydrate fractions strongly activated dendritic cells via the receptor protein TLR4. Conclusion: Composition of the lignin-carbohydrate, especially the characteristic distribution of neutral sugars, is essential for the immunostimulatory activity. Significance: Immunostimulatory lignin-carbohydrates could be potentially used as anti-infectious agents and as va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
3

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 47 publications
0
20
0
3
Order By: Relevance
“…We previously reported that LREL strongly activated DCs, in vitro, via TLR4 [ 6 ], however, it was not determined whether LREL could activate innate immunity in vivo. To determine the activity of LREL, C57BL6/J mice were intraperitoneally (i.p.)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously reported that LREL strongly activated DCs, in vitro, via TLR4 [ 6 ], however, it was not determined whether LREL could activate innate immunity in vivo. To determine the activity of LREL, C57BL6/J mice were intraperitoneally (i.p.)…”
Section: Resultsmentioning
confidence: 99%
“…Due to the molecular complexity, stable preparations of lignin-carbohydrates have proved to be difficult, and very little attention has been paid to the biological activities of lignin-containing substances. We previously found that lignin-rich enzyme lignin (LREL), one of the fractions extracted from edible plant tissues which contains lignin-carbohydrate, was able to activate bone marrow derived dendritic cells (BM-DCs) and its activity was comparable to LPS [ 6 ]. In addition, LREL derived from barley husk was shown to activate BM-DCs via toll-like receptor 4 (TLR4) [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…This suggested that CD4 signal alone could not induce sufficient stimulus to leukocytes. Recently, another research team revealed that lignin-carbohydrates isolated from barley could activate dendritic cells via TLR4 [32]. This suggests that C3H/HeJ mice-derived dendritic cells might not react to lignin-like polyphenols because of its point mutation in the TLR4 gene.…”
Section: Discussionmentioning
confidence: 98%
“…BM cells were isolated from C57BL/6 J female mice by conventional methods 35 and suspended at 1.0 × 10 6 cells/mL in DC culture medium composed of complete RPMI 1640, 10% heat-inactivated FCS (Invitrogen, CA, USA), 2.5 mM 4-(2-hydroxyethyl)-1-piperazineethanesulfonic acid (HEPES) buffer (Invitrogen), 1 mM sodium pyruvate (Invitrogen), 50 μM 2-mercaptoethanol (Invitrogen), 1% non-essential amino acids (NEAA, Invitrogen), 100 U/mL of penicillin, and 100 μg/mL of streptomycin (Sigma, MO, USA). The cells were cultured in the presence of 100 ng/mL of Flt-3L (R&D systems, MN, USA) and test extracts, fractions, and compounds were maintained at 37 °C in a 5% CO 2 atmosphere.…”
Section: Methodsmentioning
confidence: 99%